A diaphragm for solid electrolyte of lithium battery and preparation method thereof
By adding a composite electrolyte with surface grafted polymer brushed magnesium borate nanowires to the solid electrolyte membrane of lithium batteries, the problem that solid electrolyte in lithium batteries is easily broken down by lithium dendrites is solved, and a solid electrolyte membrane with high ionic conductivity and long life is achieved.
Patent Information
- Application Number
- CN202210409670.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-04-19
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2042-04-19
AI Technical Summary
The organic liquid electrolyte used in existing lithium batteries is flammable, and the solid electrolyte separator of all-solid lithium batteries is easily broken down by lithium dendrites, resulting in a short circuit and a short service life.
A composite electrolyte composed of lithium salt, polymer electrolyte, metal oxide, surfactant, binder and solvent is used to prepare a solid electrolyte membrane with surface grafted polymer brushed magnesium borate nanowires to enhance the ionic conductivity and mechanical properties of the electrolyte.
It significantly improves the ionic conductivity and room temperature stability of the solid electrolyte separator, avoids the problems of lithium dendrites and battery short circuits, and extends the service life of the battery.
Smart Images

Figure BDA0003603215580000111 
Figure BDA0003603215580000112 
Figure BDA0003603215580000121
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of lithium ion batteries, and in particular relates to a diaphragm for a lithium battery solid electrolyte and a preparation method thereof. Background Art
[0002] The development of electric vehicles, large-scale energy storage, and micro-devices requires the continuous improvement of the energy density and power density of existing secondary batteries. In the past few decades, lithium-ion batteries have attracted great attention due to their advantages such as light weight, small size, and high energy density. However, the flammable organic liquid electrolytes used in traditional lithium-ion batteries may cause serious safety problems. In addition, the large-scale application of lithium batteries, such as new energy electric vehicles, smart grids, and large-scale energy storage, also faces unprecedented challenges in terms of safety. Although various new electrolytes and protection measures are currently used, the flammable nature of organic electrolytes cannot be fundamentally solved.
[0003] All-solid-state lithium batteries based on non-flammable solid electrolytes are ideal solutions to the above problems. They can fundamentally solve the fatal disadvantage of traditional batteries being flammable. At the same time, the existing lithium battery industry is compatible with the production and application of all-solid-state lithium batteries. Therefore, all-solid-state lithium batteries have become the most promising electrochemical energy storage device and have received widespread attention in recent years. For all-solid-state lithium batteries, the ionic conductivity of the solid electrolyte diaphragm is directly related to its thickness. The thinner the thickness, the higher its ionic conductivity. However, during the charging process, lithium ions pass through the solid electrolyte from the positive electrode to the lithium metal negative electrode and receive electrons at the negative electrode for deposition. However, due to the uneven deposition of lithium ions, lithium dendrites will grow at the negative electrode and even penetrate the thinner solid electrolyte, thereby causing a short circuit in the battery and shortening the service life of the lithium battery. Therefore, how to prevent the solid electrolyte diaphragm from being broken down by lithium dendrites while ensuring that it has a high ionic conductivity is a technical problem that needs to be solved urgently.
[0004] Magnesium borate nanowires are a type of nanomaterial with good electrical conductivity and mechanical properties. Studies have shown that adding magnesium borate nanowires to solid-state electrolytes of lithium batteries can enhance the conductivity of the electrolyte, and compared with electrolytes without the addition of nanowires, electrolytes with the addition of magnesium borate nanowires can withstand greater stress. However, studies have also found that although magnesium borate nanowires can improve the conductivity of the electrolyte, the electrolyte cannot operate stably at room temperature. At room temperature, its cyclic stability is poor, resulting in the inability to effectively promote and apply magnesium borate nanowires in solid-state electrolytes of lithium batteries. Summary of the invention
[0005] In order to solve the above problems in the prior art, the present invention provides a diaphragm for a lithium battery solid electrolyte and a preparation method thereof.
[0006] To achieve the above object, the present invention provides the following technical solutions:
[0007] The invention provides a diaphragm for solid electrolyte of lithium battery, comprising a base film and a coating applied on the surfaces of both sides of the base film; wherein the coating on one side surface is composed of lithium salt, polymer electrolyte, metal oxide, surfactant, binder and solvent, and the coating on the other side surface is composed of lithium salt, polymer electrolyte, metal oxide, surfactant, binder, surface grafted polymer brush magnesium borate nanowire, organic tin stabilizer and solvent.
[0008] Furthermore, the base film is a PE film or a modified PE film with a thickness of 5 to 10 μm; the modified PE film is a PE film modified by grafting with lithium acrylate.
[0009] Furthermore, the lithium salt is lithium bis(trifluoromethanesulfonyl)imide, lithium hexafluorophosphate, lithium bis(fluorosulfonyl)imide or lithium perchlorate; and the polymer electrolyte is polyethylene glycol, polyvinylidene fluoride or polyacrylonitrile.
[0010] Furthermore, the metal oxide is lanthanum oxide, lithium oxide, aluminum oxide or zirconium oxide; the surfactant is an organic silicon surfactant, preferably polydimethylsiloxane; the binder is methyl methacrylate or acrylate; the solvent is N,N-dimethylformamide, N,N-dimethylacetamide or dimethyl sulfoxide; and the organic tin stabilizer is dibutyltin dimaleate.
[0011] The silicone surfactant enhances the bonding force between the solid electrolyte and the PE base film, thus preventing the solid electrolyte from falling off after coating.
[0012] Furthermore, the preparation method of the surface grafted polymer brush magnesium borate nanowires is as follows: magnesium nitrate hexahydrate and sodium tetraborate are added to water in a mass ratio of 1: (1-2), then heated to 200-250°C and kept warm for 24-36 hours, then the obtained precipitate is dried at 100°C for 4 hours, and after grinding, it is placed in a tube furnace and calcined at 700°C for 2 hours to obtain magnesium borate nanowires; the magnesium borate nanowires are dispersed in a polymer solution, and then centrifuged at 4000 rpm, dried, and then annealed at 160°C for 48 hours to obtain the surface grafted polymer brush magnesium borate nanowires.
[0013] Furthermore, the polymer used in the polymer solution includes one or more of polymethyl methacrylate, polyvinylidene fluoride, polyethylene glycol and polymethacrylic acid; the concentration of the polymer solution is 1-10 mg / ml.
[0014] Furthermore, the thickness of the coating on both sides of the base film is 5-10 μm.
[0015] The present invention also provides a method for preparing the above-mentioned diaphragm for solid electrolyte of lithium battery, comprising the following steps:
[0016] Adding lithium salt, polymer electrolyte, metal oxide, surfactant and binder into a solvent to obtain slurry 1;
[0017] Adding lithium salt, polymer electrolyte, metal oxide, surfactant, binder, surface-grafted polymer brush magnesium borate nanowires and organic tin stabilizer into a solvent to obtain slurry 2;
[0018] Slurry 1 and slurry 2 are respectively coated on both sides of the base film, with a coating thickness of 6 to 10 μm, and then dried at 100° C. for 24 hours to obtain the lithium battery solid electrolyte separator.
[0019] Furthermore, in the slurry 1, the mass ratio of lithium salt, polymer electrolyte, metal oxide, surfactant, binder and solvent is: (20-30): (20-30): (10-20): (3-8): (1-2): (60-80); in the slurry 2, the mass ratio of lithium salt, polymer electrolyte, metal oxide, surfactant, binder, surface grafted polymer brush magnesium borate nanowires, organic tin stabilizer and solvent is: (20-30): (20-30): (10-20): (3-8): (1-2): (10-20): (1-2): (60-80).
[0020] The present invention also provides a lithium battery, comprising the above-mentioned diaphragm for solid electrolyte of lithium battery.
[0021] Furthermore, the coating layer of the separator containing the surface-grafted polymer brush magnesium borate nanowires is close to the negative electrode of the lithium battery.
[0022] Compared with the prior art, the present invention has the following beneficial effects:
[0023] The solid electrolyte diaphragm prepared by the present invention using lithium salt, polymer electrolyte and metal oxide as composite electrolyte has excellent ion conductivity.
[0024] In the present invention, by adding surface-grafted polymer brush magnesium borate nanowires into the coating on the side of the solid electrolyte diaphragm close to the negative electrode of the lithium battery, not only the ionic conductivity of the electrolyte diaphragm is further enhanced, but also due to the presence of the surface-grafted polymer brush magnesium borate nanowires, the lithium ions can be fully dispersed in the process of passing through the solid electrolyte during charging, thereby inducing the lithium ions to deposit uniformly at the negative electrode, avoiding the problem of lithium dendrites growing at the negative electrode and even piercing the solid electrolyte due to uneven deposition of lithium ions at the negative electrode, causing a battery short circuit, and greatly extending the service life of the battery.
[0025] The present invention also found through research that by surface grafting polymer brush treatment on magnesium borate nanowires and adding an organic tin stabilizer to the solid electrolyte membrane, the magnesium borate nanowires can be stabilized, thereby enhancing the room temperature stability of the solid electrolyte containing magnesium borate nanowires, allowing it to operate stably at room temperature, improving its cycle stability, and facilitating the promotion and use of magnesium borate nanowires in solid electrolytes of lithium batteries. DETAILED DESCRIPTION
[0026] Now, various exemplary embodiments of the present invention are described in detail, and this detailed description should not be considered as a limitation of the present invention, but should be understood as a more detailed description of certain aspects, characteristics and embodiments of the present invention. It should be understood that the terms described in the present invention are only for describing specific embodiments and are not used to limit the present invention.
[0027] In addition, for the numerical range in the present invention, it is understood that each intermediate value between the upper and lower limits of the range is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0028] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.
[0029] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to the skilled artisan. The present invention description and examples are exemplary only.
[0030] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0031] Unless otherwise specified, the "parts" described in the present invention are all based on parts by weight.
[0032] In the following examples, the raw materials used are all commercially available.
[0033] Example 1
[0034] (1) Preparation of surface-grafted polymer brush magnesium borate nanowires: Magnesium nitrate hexahydrate and sodium tetraborate were added to water at a mass ratio of 1:1.5, and then heated to 220°C and kept warm for 36 hours. The resulting precipitate was then dried at 100°C for 4 hours, ground and calcined at 700°C in a tube furnace for 2 hours to obtain magnesium borate nanowires. The obtained magnesium borate nanowires were dispersed in a polyvinylidene fluoride dimethyl sulfoxide solution with a concentration of 2 mg / mL, and then centrifuged at 4000 rpm, dried, and annealed in an oven at 160°C for 48 hours to prepare surface-grafted polymer brush magnesium borate nanowires.
[0035] (2) adding 25 parts of lithium bis(trifluoromethanesulfonyl)imide, 20 parts of polyethylene glycol, 15 parts of lanthanum oxide, 8 parts of polydimethylsiloxane and 1 part of methyl methacrylate to 80 parts of N,N-dimethylformamide, stirring under an argon atmosphere, and mixing uniformly to obtain slurry 1;
[0036] (3) adding 25 parts of lithium bis(trifluoromethane) xanthamide, 20 parts of polyethylene glycol, 15 parts of lanthanum oxide, 8 parts of polydimethylsiloxane, 1 part of methyl methacrylate, 20 parts of the surface-grafted polymer brush magnesium borate nanowires prepared in step (1) and 2 parts of dibutyltin dimaleate to 80 parts of N,N-dimethylformamide, stirring under an argon atmosphere, and mixing evenly to obtain slurry 2;
[0037] (4) Slurry 1 and slurry 2 were respectively coated on both sides of a 5 μm thick PE base film, with a coating thickness of 8 μm. The film was then dried at 100° C. for 24 h to obtain a lithium battery separator coated with a solid electrolyte.
[0038] Example 2
[0039] (1) Preparation of surface-grafted polymer brush magnesium borate nanowires: Magnesium nitrate hexahydrate and sodium tetraborate were added to water at a mass ratio of 1:1, and then heated to 200°C and kept warm for 36 hours. The resulting precipitate was then dried at 100°C for 4 hours, ground and calcined at 700°C in a tube furnace for 2 hours to obtain magnesium borate nanowires. The obtained magnesium borate nanowires were dispersed in a polyethylene glycol aqueous solution with a concentration of 2 mg / mL, and then centrifuged at 4000 rpm, dried, and annealed in an oven at 160°C for 48 hours to prepare surface-grafted polymer brush magnesium borate nanowires.
[0040] (2) adding 30 parts of lithium hexafluorophosphate, 25 parts of polyvinylidene fluoride, 20 parts of lithium oxide, 3 parts of polydimethylsiloxane and 1.5 parts of acrylate to 60 parts of N,N-dimethylacetamide, stirring under an argon atmosphere, and mixing uniformly to obtain slurry 1;
[0041] (3) adding 30 parts of lithium hexafluorophosphate, 25 parts of polyvinylidene fluoride, 20 parts of lithium oxide, 3 parts of polydimethylsiloxane, 1.5 parts of acrylate, 10 parts of the surface-grafted polymer brush magnesium borate nanowires prepared in step (1) and 1 part of dibutyltin dimaleate to 60 parts of N,N-dimethylacetamide, stirring under an argon atmosphere, and mixing evenly to obtain slurry 2;
[0042] (4) Slurry 1 and slurry 2 were respectively coated on both sides of a PE base film with a thickness of 8 μm, with a coating thickness of 10 μm. The film was then dried at 100° C. for 24 h to obtain a lithium battery separator coated with a solid electrolyte.
[0043] Example 3
[0044] (1) Preparation of surface-grafted polymer brush magnesium borate nanowires: Magnesium nitrate hexahydrate and sodium tetraborate were added to water in a mass ratio of 1:2, and then heated to 250°C and kept warm for 24 hours. The resulting precipitate was then dried at 100°C for 4 hours, ground and calcined at 700°C in a tube furnace for 2 hours to obtain magnesium borate nanowires. The obtained magnesium borate nanowires were dispersed in a polymethacrylic acid aqueous solution with a concentration of 2 mg / mL, and then centrifuged at 4000 rpm, dried, and annealed in an oven at 160°C for 48 hours to prepare surface-grafted polymer brush magnesium borate nanowires.
[0045] (2) adding 20 parts of lithium perchlorate, 30 parts of polyacrylonitrile, 10 parts of zirconium oxide, 5 parts of polydimethylsiloxane and 2 parts of methyl methacrylate to 70 parts of dimethyl sulfoxide, stirring under an argon atmosphere, and mixing well to obtain slurry 1;
[0046] (3) adding 20 parts of lithium perchlorate, 30 parts of polyacrylonitrile, 10 parts of zirconium oxide, 5 parts of polydimethylsiloxane, 2 parts of methyl methacrylate, 15 parts of the surface-grafted polymer brush magnesium borate nanowires prepared in step (1) and 1.5 parts of dibutyltin dimaleate to 70 parts of dimethyl sulfoxide, stirring under an argon atmosphere, and mixing evenly to obtain slurry 2;
[0047] (4) Slurry 1 and slurry 2 were respectively coated on both sides of a 10 μm thick PE base film, with the coating thickness being 10 μm. The film was then dried at 100° C. for 24 h to obtain a lithium battery separator coated with a solid electrolyte.
[0048] Example 4
[0049] (1) Preparation of surface-grafted polymer brush magnesium borate nanowires: Magnesium nitrate hexahydrate and sodium tetraborate were added to water at a mass ratio of 1:1.5, and then heated to 220°C and kept warm for 36 hours. The resulting precipitate was then dried at 100°C for 4 hours, ground and calcined at 700°C in a tube furnace for 2 hours to obtain magnesium borate nanowires. The obtained magnesium borate nanowires were dispersed in a 2 mg / mL polymethyl methacrylate chloroform solution, and then centrifuged at 4000 rpm, dried, and annealed in an oven at 160°C for 48 hours to prepare surface-grafted polymer brush magnesium borate nanowires.
[0050] (2) Preparation of modified PE film: a PE film with a thickness of 5 μm and a length and width of 5 cm is placed in a container, 20 mL of a 10 wt% lithium acrylate solution is prepared, and then 20 mL of a TX-10 surfactant is added. The solution is added to the container containing the PE film, shaken, and protected from light to allow the solution to completely wet the PE film. After 1 hour, the solution is poured out and the film is vacuum-sealed and irradiated under a high-energy electron beam with an irradiation dose of 18 kGy. The film is then taken out and boiled with distilled water for 30 minutes, and the surface of the film is cleaned with distilled water to remove unreacted lithium acrylate. The film is then washed with distilled water and placed in an oven and dried at 100° C. for 1 hour to obtain a modified PE film.
[0051] (3) adding 25 parts of lithium bis(trifluoromethanesulfonyl)imide, 20 parts of polyethylene glycol, 15 parts of lanthanum oxide, 8 parts of polydimethylsiloxane and 1 part of methyl methacrylate to 80 parts of N,N-dimethylformamide, stirring under an argon atmosphere, and mixing uniformly to obtain slurry 1;
[0052] (4) adding 25 parts of lithium bis(trifluoromethane) xanthamide, 20 parts of polyethylene glycol, 15 parts of lanthanum oxide, 8 parts of polydimethylsiloxane, 1 part of methyl methacrylate, 20 parts of the surface-grafted polymer brush magnesium borate nanowires prepared in step (1) and 2 parts of dibutyltin dimaleate to 80 parts of N,N-dimethylformamide, stirring under an argon atmosphere, and mixing evenly to obtain slurry 2;
[0053] (5) Slurry 1 and slurry 2 are respectively applied to the two side surfaces of the modified PE film prepared in step (2), with the coating thickness of 8 μm, and then dried at 100° C. for 24 h to obtain a lithium battery separator coated with a solid electrolyte.
[0054] Comparative Example 1
[0055] The same as Example 1, except that in step (3), no surface-grafted polymer brush magnesium borate nanowires are added.
[0056] Comparative Example 2
[0057] Same as Example 1, except that dibutyltin dimaleate is not added in step (3).
[0058] Comparative Example 3
[0059] Same as Example 1, except that step (1) is:
[0060] Preparation of magnesium borate nanowires: Magnesium nitrate hexahydrate and sodium tetraborate are added to water in a mass ratio of 1:1.5, then heated to 220°C and kept warm for 36 hours, and then the resulting precipitate is dried at 100°C for 4 hours, ground and placed in a tube furnace for high-temperature roasting at 700°C for 2 hours to obtain magnesium borate nanowires. At the same time, the "20 portions of surface-grafted polymer brush magnesium borate nanowires prepared in step (1)" in step (3) are replaced with "20 portions of magnesium borate nanowires prepared in step (1)". That is, in this comparative example, when preparing the electrolyte diaphragm, the magnesium borate nanowires added are not treated with polymer brush grafting.
[0061] Effect verification
[0062] 1. The ionic conductivity of the lithium battery diaphragm coated with solid electrolyte prepared in Examples 1 to 4 and Comparative Examples 1 to 3 was tested: a model battery composed of stainless steel electrode / lithium battery diaphragm coated with solid electrolyte / stainless steel electrode was used, the AC impedance was measured at 25°C, and the ionic conductivity was calculated according to the formula: Ionic conductivity = diaphragm thickness / (AC impedance value × contact area between electrode and diaphragm). The results are shown in Table 1.
[0063] Table 1
[0064]
[0065] It can be seen from Table 1 that after adding surface-grafted polymer brush magnesium borate nanowires to the solid electrolyte, the room temperature ionic conductivity of the solid electrolyte is significantly improved, and after modifying the PE base film, the ionic conductivity of the solid electrolyte is also improved to a certain extent.
[0066] 2. Lithium iron phosphate is used as the positive electrode material and lithium is used as the negative electrode material, and a battery is assembled with the lithium battery separator coated with a solid electrolyte prepared in Examples 1 to 4 and Comparative Examples 1 to 3, so that the coating containing the surface grafted polymer brush magnesium borate nanowires or magnesium borate nanowires of the separator is close to the negative electrode (in Comparative Example 1, the coating containing dibutyltin dimaleate of the separator is close to the negative electrode), and the other side is close to the positive electrode. After assembly, the test is carried out according to the following method: 1) charging at 0.2C, the cut-off voltage is 4.2V; 2) charging at a constant voltage of 4.2V, the cut-off current is 0.05C; 3) discharging at 0.2C, the cut-off voltage is 3V; repeat the above steps 1) to 3), record the number of cycles and the corresponding capacity retention rate, and the results are shown in Table 2.
[0067] Table 2
[0068]
[0069]
[0070] It can be seen from Table 2 that the addition of surface-grafted polymer brush magnesium borate nanowires to the solid electrolyte can extend its service life, and the addition of organic tin stabilizer can make the solid electrolyte operate stably at room temperature, significantly improve the capacity retention rate, and improve the room temperature cycle stability.
[0071] The above description is only a preferred specific implementation manner of the present invention, and the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, and they should be covered by the protection scope of the present invention.
Claims
1. A diaphragm for a lithium battery solid electrolyte, characterized in that: The invention comprises a base film and a coating applied on both sides of the base film; the coating on one side is composed of lithium salt, polymer electrolyte, metal oxide, surfactant, binder and solvent, and the coating on the other side is composed of lithium salt, polymer electrolyte, metal oxide, surfactant, binder, surface grafted polymer brush magnesium borate nanowire, organic tin stabilizer and solvent; the preparation method of the surface grafted polymer brush magnesium borate nanowire is as follows: magnesium nitrate hexahydrate and sodium tetraborate are added into water in a mass ratio of 1: (1-2), and then The method comprises the steps of heating the precipitate to 200-250° C. and keeping the temperature for 24-36 hours, drying the precipitate, grinding the precipitate, and calcining the precipitate in a tube furnace at 700° C. for 2 hours to obtain magnesium borate nanowires; dispersing the magnesium borate nanowires in a polymer solution, centrifuging, drying, and annealing to obtain the surface-grafted polymer brush magnesium borate nanowires; the polymer used in the polymer solution comprises one or more of polymethyl methacrylate, polyvinylidene fluoride, polyethylene glycol, and polymethacrylic acid; and the organic tin stabilizer is dibutyltin dimaleate.
2. The lithium battery solid electrolyte separator according to claim 1, characterized in that: The base film is a PE film or a modified PE film with a thickness of 5 to 10 μm; the modified PE film is a PE film modified by grafting with lithium acrylate.
3. The diaphragm for lithium battery solid electrolyte according to claim 1, characterized in that: The lithium salt is lithium bis(trifluoromethanesulfonyl)imide, lithium hexafluorophosphate, lithium bis(fluorosulfonyl)imide or lithium perchlorate; and the polymer electrolyte is polyethylene glycol, polyvinylidene fluoride or polyacrylonitrile.
4. The lithium battery solid electrolyte separator according to claim 1, characterized in that: The metal oxide is lanthanum oxide, lithium oxide or zirconium oxide; the surfactant is an organic silicon surfactant; the binder is methyl methacrylate or acrylate; and the solvent is N,N-dimethylformamide, N,N-dimethylacetamide or dimethyl sulfoxide.
5. The lithium battery solid electrolyte separator according to claim 1, characterized in that: The thickness of the coatings on both sides of the base film is 5-10 μm.
6. A method for preparing a diaphragm for a lithium battery solid electrolyte according to any one of claims 1 to 5, characterized in that: The following steps are involved: Adding lithium salt, polymer electrolyte, metal oxide, surfactant and binder into a solvent to obtain slurry 1; Adding lithium salt, polymer electrolyte, metal oxide, surfactant, binder, surface-grafted polymer brush magnesium borate nanowires and organic tin stabilizer into a solvent to obtain slurry 2; The slurry 1 and slurry 2 are respectively coated on the surfaces of both sides of the base film, and then dried to obtain the separator for the solid electrolyte of the lithium battery.
7. The preparation method according to claim 6, characterized in that: In the slurry 1, the mass ratio of lithium salt, polymer electrolyte, metal oxide, surfactant, binder and solvent is: (20-30): (20-30): (10-20): (3-8): (1-2): (60-80); in the slurry 2, the mass ratio of lithium salt, polymer electrolyte, metal oxide, surfactant, binder, surface grafted polymer brush magnesium borate nanowires, organic tin stabilizer and solvent is: (20-30): (20-30): (10-20): (3-8): (1-2): (10-20): (1-2): (60-80).
8. A lithium battery, characterized in that: A diaphragm for a lithium battery solid electrolyte comprising any one of claims 1 to 5.
9. The lithium battery according to claim 8, characterized in that: The coating layer of the separator containing surface-grafted polymer brush magnesium borate nanowires is close to the negative electrode of the lithium battery.
Citation Information
Patent Citations
Method for surface modification of magnesium borate crystal whisker by using borate coupling agent
CN102321395A
Surface modification method for magnesium borate whiskers
CN106400486A